Ideology and evolution in nineteenth century Britain - Richards, Evelleen, author.
1 online resource.
Keywords: "Written over several decades and collected together for the first time, these richly detailed contextual studies by a leading historian of science examine the diverse ways in which cultural values and political and professional considerations impinged upon the construction, acceptance and applications of nineteenth century evolutionary theory. They include a number of interrelated analyses of the highly politicised roles of embryos and monsters in pre- and post- Darwinian evolutionary theorizing, including Darwin's; several studies of the intersection of Darwinian science and its practitioners with issues of gender, race and sexuality, featuring a pioneering contextual analysis of Darwin's theory of sexual selection; and explorations of responses to Darwinian science by notable Victorian women intellectuals, including the crusading anti-feminist and ardent Darwinian, Eliza Lynn Linton, the feminist and leading anti-vivisectionist Frances Power Cobbe, and Annie Besant, the bible-bashing, birth-control advocate who confronted Darwin's opposition to contraception at the notorious Knowlton Trial"--